2021
DOI: 10.1021/acsomega.1c00560
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Crystalline Biofilm Formation on Superhydrophobic Silicone Urinary Catheter Materials

Abstract: Crystalline biofilm formation in indwelling urinary catheters is a serious health problem as it creates a barrier for antibacterial coatings. This emphasizes the failure of antibacterial coatings that do not have a mechanism to reduce crystal deposition on catheter surfaces. In this study, trifluoropropyl spray-coated polydimethylsiloxane (TFP–PDMS) has been employed as an antibiofilm forming surface without any antibacterial agent. Here, TFP was coated on half-cured PDMS using the spray coating technique to o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 66 publications
0
15
0
Order By: Relevance
“…Trifluoropropyl spray‐coated polydimethylsiloxane was employed as a superhydrophobic urine antibacterial surface by Gayani and his partner. [ 148 ] Cycled for 14 days under flowing conditions, the superhydrophobic trifluoropropyl‐PDMS urinary catheters exhibited less biofilm than commercially available silicone catheters.…”
Section: Application Of Sbfrssmentioning
confidence: 99%
“…Trifluoropropyl spray‐coated polydimethylsiloxane was employed as a superhydrophobic urine antibacterial surface by Gayani and his partner. [ 148 ] Cycled for 14 days under flowing conditions, the superhydrophobic trifluoropropyl‐PDMS urinary catheters exhibited less biofilm than commercially available silicone catheters.…”
Section: Application Of Sbfrssmentioning
confidence: 99%
“…Cytotoxicity was determined by MTT assay and represented as the percentage of remaining viable cells after treatment. impregnation with compounds that resist the formation of crystalline biofilm became the focus of recent studies to reduce the incidence of CAUTI (Liu et al, 2019;Gayani et al, 2021;Koc et al, 2021). Many studies suggested the utilization of antimicrobials for coating the catheters to inhibit the growth of bacteria on the surface.…”
Section: A B Figurementioning
confidence: 99%
“…Scientists have been searching for new methods for the implementation of biofilm-free catheters. These methods include modifying catheter materials (Pathak et al, 2018;Gayani et al, 2021); coating and impregnating catheters with antimicrobial (Monteiro et al, 2019;Yassin et al, 2019) and antibiofilm compounds (Liu et al, 2019;Swidan et al, 2022). Antivirulence and antibiofilm compounds are attracting more interest recently because they affect bacterial virulence without creating selection pressure and thus reducing the development of antibiotic resistance.…”
Section: Introductionmentioning
confidence: 99%
“…The most commonly used low surface energy molecules to form superhydrophobic surfaces include fluorocarbon chains such as trifluoropropyl [ 11 ], polytetrafluoroethylene [ 12 ], and 1H, 1H, 2H, 2H-perfluorodecanethiol [ 13 ]. In a study by John et al [ 14 ], nanoimprint lithography with a low surface energy molecule, 1H,1H,2H,2H-perfluorodecyl acrylate was utilised to form superhydrophobic surfaces which performed to confer the surface anti-biofouling properties against E. coli .…”
Section: Introductionmentioning
confidence: 99%